Relationship between interdisciplinarity and transdisciplinarity: an essentially contested concept perspective. - Aliyeva, Sevinj Sardar (Innovation: The European Journal of Social Sciences, 2026)
This article focuses on interdisciplinary/transdisciplinary relationships that are analyzed rather as mutually exclusive variables with different ontological and logico-epistemological dimensions, properties and attributes. Interdisciplinarity is treated as an independent variable (cause), while transdisciplinarity is considered as a dependent variable (effect) in the structure of the 'causal logic', which has been confused with the 'ontological causation' in numerous researches. Our analysis of academic literature shows that the studies in interdisciplinarity and its types have been mostly studied separately, while the problem of the relationship between interdisciplinary/transdisciplinary categories, particularly the correlation between them, has not become yet the subject of a study on the level of categories and conceptions. Why does this problem arise? We are witnessing a new trend in which many researchers try to adapt interdisciplinary/transdisciplinary concepts to more phenomena and cultural contexts. In doing so, they usually expand or narrow the extensional and intensional definitions of these categories, contrast the one with the other or show the superiority of the one over the other. This is where the problem of our research emerges. This article shows the ways for evading the challenges of the conceptual stretching and promoting the advantages of the conceptual expanding of interdisciplinary/transdisciplinary relationship and interplay.